Pengaruh Aset, Status Kewarganegaraan, dan Pengalaman Dewan Terhadap Net Profit Margin dengan Sales dan Good Corporate Governance Sebagai Variabel Intervening - Jeremy Evan Yusuf; Amelia Setiawan (J-CEKI : Jurnal Cendekia Ilmiah, 2025)
This study aims to analyze the effect of assets, citizenship status, and board experience on net profit margin (NPM) with sales and good corporate governance (GCG) as intervening variables. The research method used is quantitative with a causal approach to understanding the cause-and-effect relationship between variables. The data used includes secondary data from the annual reports of consumer cyclicals and non-cyclicals companies listed on the Indonesia Stock Exchange (IDX) for the period 2022-2023. The results show that foreign citizenship status and board experience have a negative effect on GCG, while assets have a positive effect on sales. GCG and sales each have a negative influence on NPM. This finding indicates that while assets may increase sales, the cost of GCG implementation and certain sales strategies may suppress the company's profit margin. This study provides recommendations for companies to optimally utilize assets, improve the effectiveness of GCG implementation with cost efficiency, and manage a balanced sales strategy to maintain profitability.